Optimizing irrigation efficiency: a case study of the Bakbakti Rice System in Akdala Massif - Absametov, Malis; Umbetaliev, Dauren; Kulagin, Vitaly; Rakhimov, Timur; Mirlas, Vladimir; Ismagulova, Aida; Rakhimova, Valentina (Frontiers in Water, 2025)
IntroductionWater scarcity increasingly limits irrigated agriculture in arid and semi-arid regions, particularly in Kazakhstan's northernmost rice-growing zone, the Akdala irrigation massif of the Ile River basin. This study examines the feasibility of reusing collector-drainage water, together with groundwater and surface water, to reduce freshwater deficits in the Tasmurun section of the Bakbakty system.MethodsField experiments were conducted from 2022 to 2024 on two rice fields (311 ha) to evaluate water and salt balances, soil and groundwater dynamics, and water-saving irrigation technologies. The irrigation regime incorporated 25–30% collector-drainage water and was compared to a 2022 freshwater control.ResultsThe mixed-source irrigation approach reduced freshwater withdrawals by 14% (1.674 million m3 annually) and lowered the irrigation norm from 26,082 to 22,900 m3/ha. Soil and groundwater quality indicators remained stable, and rice yields increased by 6.8–9.2%. Economic efficiency rose by 25%, with farm profitability reaching 35%.DiscussionThe findings confirm that on-farm reuse of collector-drainage water is a viable, environmentally safe strategy for offsetting irrigation deficits and reducing anthropogenic pressure on transboundary water resources. As the first field-validated study of its kind in Kazakhstan, this research presents a novel technology that avoids the negative impacts of diverting drainage water into river channels and provides practical balance parameters for adapting irrigation systems under water scarcity. The rational reuse of collector-drainage water offers a sustainable pathway to strengthen water security, support rice cultivation, and enhance economic resilience in Kazakhstan's vulnerable semi-desert regions.